2021
DOI: 10.1108/jaee-02-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Public sector accounting in emerging economies: a review of the papers published in the first decade of Journal of Accounting in Emerging Economies

Abstract: PurposeA review of papers on public sector accounting in emerging economies, as published in the Journal of Accounting in Emerging Economies' (JAEE) first decade.Design/methodology/approachA reflection on the issues covered and achievements made in the reviewed papers in the context of extant knowledge in this domain.FindingsA majority of the research in JAEE is dominated by accounting reforms inspired by New Public Management (NPM). Performance management, budgeting and accrual accounting are the main topics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 71 publications
(169 reference statements)
1
52
1
4
Order By: Relevance
“…The new special issue, edited by Adhikari et al (2021), of Journal of Accounting in Emerging Economies ( JAEE ) sheds light on unintended consequences of NPM reforms in the process of adopting new accounting and budgeting practices. A review of van Helden et al (2021) on PSA in emerging economies shows that many papers attempt to explain failing accounting innovations with reference to the local context in which they are embedded, including political instability, poor governance and a lack of capabilities. The specific reviews on International Public Sector Accounting Standards (IPSASs) adoption in emerging economies conducted by Polzer et al (2022a, 2022b) offer a holistic understanding of where and at what stages reforms stand in emerging economies, and what factors influence the progression of reforms to the next stage of diffusion.…”
Section: Public Sector Accounting Research: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The new special issue, edited by Adhikari et al (2021), of Journal of Accounting in Emerging Economies ( JAEE ) sheds light on unintended consequences of NPM reforms in the process of adopting new accounting and budgeting practices. A review of van Helden et al (2021) on PSA in emerging economies shows that many papers attempt to explain failing accounting innovations with reference to the local context in which they are embedded, including political instability, poor governance and a lack of capabilities. The specific reviews on International Public Sector Accounting Standards (IPSASs) adoption in emerging economies conducted by Polzer et al (2022a, 2022b) offer a holistic understanding of where and at what stages reforms stand in emerging economies, and what factors influence the progression of reforms to the next stage of diffusion.…”
Section: Public Sector Accounting Research: An Overviewmentioning
confidence: 99%
“…At least three different development discourses have been identified over the years, and researchers have mainly focused on showing how different accounting technologies have been embedded in these discourses (van Helden and Uddin, 2016). More recently, van Helden et al (2021) identified a lack of limited accounting research on the ways in which different accounting technologies have been involved in state-led developments. Instead, extant work has mostly covered the NPM-driven market-led development discourses in which accounting technologies such as accrual accounting and IPSASs, long-term budgeting and performance reporting and auditing have served as key technical tools through which to improve governance and accountability and facilitate economic advancement (van Helden et al , 2021; Kuruppu et al , 2021).…”
Section: Perspectives On Public Sector Accountingmentioning
confidence: 99%
See 2 more Smart Citations
“…Another quarter draw on new institutional theory (Greenwood et al, 2017). Also, the overview by Van Helden et al (2021) finds that this theory has dominated PSA research in EEs and LICs in the last decade. Here, a number of studies delve into the different aspects of isomorphism, for example how international donors and organisations exert pressures to implement IPSASs.…”
Section: Jpbafmmentioning
confidence: 99%